Height and weight changes after deep brain stimulation in patients with Parkinson disease: role of clinical subtypes. Issue 6 (June 2019) - Abboud, Hesham; Reyes, Dennys; Genc, Gencer; Ahmed, Anwar; Gostkowski, Michal; Fernandez, Hubert H.
Abstract: Increased body mass index (BMI) after deep brain stimulation (DBS) in Parkinson's disease (PD) has been repeatedly reported in literature. However, little is known about the effect of PD clinical subtypes on weight and height changes after DBS. We aimed to study the differential effect of tremor-predominant versus hypokinetic-rigid disease on weight and height changes after DBS. Methodology: we chart-reviewed PD patients who underwent DBS at our center from 2006 to 2011. Weight and height data were obtained at the pre-surgical period, at 1-year post-surgery, and at the latest available follow-up (LAF). Results: There were 130 patients in the dataset (70% male, mean age 63+/-9.1). Eighty-eight patients had available data at 1-year post-DBS or longer. Mean LAF was 4.36+/-1.64 years. A BMI increment by 1 Kg/m2 or more was noticed in 35% after 1-year. Increased height (1cm-or-more) was seen in 24% of patients at 1-year. At 1-year post-DBS, 41.8% of patients with hypokinetic-rigid subtype increased in height compared to only 14.2% in the tremor-predominant group (OR 4.3, 95 % CI 1.3167-14.1246, P=0.015). There was no correlation between PD subtype and weight change after DBS. Conclusion: This study confirms BMI increase after DBS in PD patients and reports a novel finding of increased height after DBS in patients with hypokinetic-rigid PD. This might be secondary to improved axial rigidity following DBS. Resolution of tremor is probably unrelated to the increase in body weight after surgery since weight gain did not differ between patients with tremor-predominant and those with hypokinetic-rigid subtype.